2013
DOI: 10.12816/0000748
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Vitamin D Deficiency among Men

Abstract: Background: Vitamin D is vital for human health but its deficiency is worldwide. There is a gap in our knowledge about vitamin D status in Bahrain. Objective: To identify vitamin D status and associated risk factors among men in Bahrain. Design: A cross-sectional study. Setting: Four public and four private maternity hospitals in Bahrain. Method: The study was carried out in the second and third weeks of April 2012. Three hundred sixty-four men (husbands of mothers who presented in labor) participated in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Two studies from Bahrain revealed the extent of hypovitaminosis D among adults and mothers and their newborns in the labor room. Both studies addressed the controversies that entails the diagnosis and management of hypovitaminosis D and highlighted a striking fact of high prevalence of hypovitaminosis D in a very sunny community like Bahrain [14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies from Bahrain revealed the extent of hypovitaminosis D among adults and mothers and their newborns in the labor room. Both studies addressed the controversies that entails the diagnosis and management of hypovitaminosis D and highlighted a striking fact of high prevalence of hypovitaminosis D in a very sunny community like Bahrain [14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…The Bahrain nutritional survey published in 1995 addressed the need to estimate the prevalence of micronutrients' deficiencies including vitamin D 13 . In 2013 and 2014, four studies were published in Bahrain, which highlighted the prevalence of hypovitaminosis D and the impact of the deficiency if any [14][15][16][17] . These studies revealed a high prevalence of hypovitaminosis D ranging from 60%-90%, a predilection for females and associated with lack of sun exposure, smoking and high BMI.…”
mentioning
confidence: 99%
“…Some studies used adapted versions of established instruments to assess emotional violence by teachers, for instance the Conflict Tactic Scales (e.g., Elbedour et al, 1997; Hecker et al, 2018; Kızıltepe et al, 2020) and the Child Abuse Screening Tool of the International Society for the Prevention of Child Abuse and Neglect (Chandraratne et al, 2018; Devries et al, 2014; Longobardi et al, 2017). Other studies used purpose-built scales (e.g., Al Mahroos, 1997; Banzon-Librojo et al, 2017; Shumba, 2004; Theoklitou et al, 2012) or single items (Delfabbro et al, 2006; Lin et al, 2020) to assess emotional violence. Overall, 17 studies were judged to be of high, 53 studies of moderate and 14 studies of low quality.…”
Section: Resultsmentioning
confidence: 99%
“…3 They have distinguished two broad categories of CSO; which can either be paedophilic or non-pedophilic where paedophilia is characterized by a sexual deviation involving strong sexual attraction toward children. 2 He further observed that CSA perpetrators did not seem to be aware of the psychological damage that their victims suffered, yet these interactions often destroy the child's trust and ability to share intimacy even in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Only after the abused children grow-up are they able to understand that they were powerless to protect themselves and not responsible for what was done to them. 2 To reinforce this self attribution, the child might have been convinced by the perpetrator and even by those who should have been providing protection that the child itself was the cause.…”
Section: Introductionmentioning
confidence: 99%